On the subgenus Eurysunius Reitter of Turkey VI. Two new species from Sivas province in central northern Anatolia, with a key to Turkish species (Coleoptera: Staphylinidae: Paederinae, Astenus) - Anlaş Si̇nan (Zootaxa, 2019)
Two new species of Astenus (Eurysunius) Dejean (Coleoptera: Staphylinidae: Paederinae) are described and illustrated from Sivas province in central northern Turkey, and distinguished from related consubgeners: Astenus pelinae Anlaş, sp. n. (İmranlı and Divriği) and A. sivasicus Anlaş, sp. n. (Akıncılar). A key to Turkish species of Eurysunius is provided, as well as a map indicating their geographical distribution.